TMS assessment of corticospinal tract integrity after stroke: broadening the concept to inform neurorehabilitation prescription - Kumar, Sapna; Ferraro, Mary; Nguyen, Lienhoung; Cao, Ning; Ung, Nathaniel; Jose, Joshua S.; Weidenauer, Cheryl; Edwards, Dylan J.; Mayer, Nathaniel H. (Frontiers in Human Neuroscience, 2024)
Upper limb actions require intersegmental coordination of the scapula, shoulders, elbows, forearms, wrists, and hand muscles. Stroke hemiparesis, presenting as an impairment of an intersegmentally coordinated voluntary movement, is associated with altered integrity of corticospinal tract (CST) transmission from the motor cortex (M1) to muscles. Motor evoked potentials (MEPs) elicited by M1 transcranial magnetic stimulation (TMS) of “at rest” muscles, or as a backup, during muscle contraction have been used to identify CST integrity and predict the outcome after hemiparesis, under the implicit assumption that MEPs present in only one or two muscles are manifest surrogates of CST integrity for other muscles of the upper limbs. This study presents a method for applying TMS during motor tasks that involve proximal and distal muscles. It focuses on evaluating multi-muscle electromyography (EMG) and MEPs across all task-relevant limb segments. Protocols are presented for assessing voluntary motor behavior in individuals with hemiparetic stroke using isometric, unimanual, bimanual, and “REST” conditions that broaden the concept of the degree of CST integrity in order to inform clinical prescription for neurorehabilitation and distinguish its potential as a prognostic tool. Data describing the recordings of multi-muscle transcranial magnetic stimulation induced motor evoked potentials (TMS-MEP) will be presented in a case of subacute hemiparetic stroke to elucidate our perspective.